"If It's not on Strava it Didn't Happen": Perceived Psychosocial Implications of Strava use in Collegiate Club Runners. Issue 1 (April 2023) - Russell, Hayley C.; Potts, Charlie; Nelson, Emma
The fitness app Strava incorporates the utility of a fitness tracker with the connection of social media. Since 2009, Strava has attracted over 100 million users, yet little research has assessed the implications of its use. The purpose of this study was to explore the perceived psychosocial implications of Strava use among collegiate club runners. Semi-structured interviews were conducted with 18 runners from collegiate running clubs across the United States who were Strava users. Results indicated that runners perceived the psychosocial implications of Strava use to fall into three main themes: 1) self-presentation, 2) social pressure, and 3) motivation. The findings of this study support the utility of Strava to connect collegiate club runners and support their motivation to run while also suggesting some potential concerns related to social pressure and self-presentation that could influence mental or physical health.